Study on shear wave attenuation characteristics of shallow sediments in gas hydrate pilot production area of South China Sea. Issue 2 (January 2021) - Zhang, Zhenchao; Guo, Xiujun; Yang, Bin; Tang, Haoru; Lei, Shiyun; Xing, Cheng; Wu, Jingxin
Abstract: Shear wave attenuation of sediment is an important acoustic feature of seafloor sediment, which reflects the ability of sediment to absorb and dissipate shear wave energy, which is closely related to sediment structure. In order to explore the change rule and influencing factors of shear wave attenuation in sediments, the absorption coefficient was selected as the characterization of shear wave attenuation characteristics, and unconsolidated undrained triaxial shear tests were carried out with two typical sediment silty sand and fine sand in Shenhu sea area of South China Sea as samples. Through comparative analysis, the experimental results show that the shear wave absorption coefficient of sediment is in the process of shear failure at first, it fluctuated slightly, then gradually stabilized, and finally continued to rise in the fluctuation. The shear wave absorption coefficient increases with the increase of porosity and decreases with the increase of confining pressure. In addition, the relationship between the shear wave absorption coefficient and the undrained shear strength of sediment presents a quadratic function. The smaller the shear wave absorption coefficient is, the higher the undrained shear strength of sediment is.